PURIFICATION OF STEVIA SWEETENER BY CROSSFLOW ULTRAFILTRATION - Erliza Noor dan Fifi Isdianti (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTCrossflow ultrafiltration membrane was applied to stevia extract solution for removing non-sugar impurities and maintain the sugars content, especially stevioside, rebaudioside and steviolbiside that have molecular weight below 1 kDa. The impurities such as chlorophyll, alkaloid, tannin, steroid, flavonoid gave unclear solution. The ultrafiltration used was a hollow fiber module equipped by polyethersulfone (PES) membrane with the pore size of 20 kDa. The ultrafiltration could remove the impurities indicated by a low ash content in the permeate and increase solution clarity. The high clarification was obtained at crossflow velocity of 0.02 m/s and transmembrane pressure at 1.87 bars. These conditions gave highest flux of 60 L/m2.h and lowest stevioside rejection of 36%. The solution clarity increased up to 64%, whereas the ash content decreased by 62%.  Keywords: stevia, crossflow ultrafiltration membrane